Peningkatan Kualitas Pelayanan Publik melalui Inovasi Berbasis Ekologi Administrasi di Indonesia - Jein Lusiana Togatorop; Eko Nuriyatman; Arrie Budhiartie (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
Public service is a tangible manifestation of the state's function in meeting the needs and basic rights of the community but, in practice, public services in Indonesia still face various challenges such as rigid bureaucracy, low quality of services, and weak coordination between institutions. The ecological approach to administration exists as a new paradigm that emphasizes the interrelationships between bureaucratic structures, the social environment, culture and Natural Resources.The development of public services through an ecological perspective in Indonesia emphasizes the importance of conformity between the bureaucratic system and the conditions of the social environment in order to create adaptive, participative, and sustainable public services. This method used is a descriptive qualitative study by examining a variety of legal literature, as well as the practice of service innovation in some in Indonesia.Public service innovation based on ecology administration is able to create harmony between government, society and the environment and encourage the creation of adative governance and responsive to local needs through this application to strengthen collaboration across several sectors.